Efficacy of specimen pasting after cold snare polypectomy for pathological evaluation of horizontal margins - Ikeda, Takuya; Yoshizaki, Tetsuya; Eguchi, Takaaki; Kinugasa, Hiroshi; Okada, Akihiko (Endoscopy International Open, 2022)
Background and study aims Several studies have reported that pathological horizontal margin evaluation cannot be diagnosed in cold snare polypectomy (CSP) specimens. We conducted a prospective randomized controlled trial to determine the efficacy of pasting CSP specimens on paper for pathological horizontal margins.Patients and methods This was a single-center, prospective study conducted at Osaka Saiseikai Nakatsu Hospital. In this study, the indications for CSP were adenomas ≤ 10 mm. Colorectal polyps resected by CSP were randomized to the pasting and non-pasting groups after exclusion of fragmented specimens, and the extended CSP specimens pasted on paper were formalin-fixed in the pasting group. The primary endpoint was rate of unclear horizontal margins after CSP.Results A total of 216 CSP specimens were analyzed. The rate of unclear horizontal margins was significantly lower in the pasting group than in the non-pasting group (15.1 % vs 33.6 %, P = 0.002). CSP specimen pasting significantly reduced the rate of unclear horizontal margins. On multivariate analysis, non-pasting group (odds ratio [OR], 2.69; 95 % confidence interval [CI], 1.38–5.41; P = 0.003) and right colon (OR, 1.98; 95 %CI, 1.01–4.01; P = 0.047) were independent risk factors for unclear horizontal margins in CSP specimens.Conclusions Pasting the extended specimen is important for accurate pathological examination after CSP.